Caribbean golden orbweaving spiders maintain gene flow with North America. (19th January 2020) - Čandek, Klemen; Agnarsson, Ingi; Binford, Greta J.; Kuntner, Matjaž
Abstract: The Caribbean archipelago offers one of the best natural arenas for testing biogeographic hypotheses. The intermediate dispersal model of biogeography (IDM) predicts variation in species richness among lineages on islands to relate to their dispersal potential. To test this model, one would need background knowledge of dispersal potential of lineages and their biogeographic patterns, which has been problematic as evidenced by our prior work on the Caribbean tetragnathid spiders. In order to investigate the biogeographic imprint of an excellent disperser, we study Trichonephila in the Americas. Trichonephila is a nephilid genus that contains globally distributed species known to overcome long, overwater distances. The results of our phylogenetic and population genetic analyses on T. clavipes suggest that populations over the Caribbean and North America maintain a lively gene flow. However, the single species status of T. clavipes over the entire New World is challenged by our species delimitation analyses. Combined with prior evidence from spider genera of different dispersal ability, these patterns coming from an excellent disperser ( Trichonephila ) that is species‐poor and of a relatively homogenous genetic structure, support the IDM predictions.